Drying ripe mango slices using step-down temperature far-infrared-hot air techniques - Paengkanya, Suwit; Patcharatvirakul, Sutinon; Kumklam, Ponlakrit (International Journal of Agricultural and Biological Engineering, 2025)
A key challenge in food drying is achieving an optimal balance between processing efficiency, energy consumption, and maintaining high quality in the final product. This study investigates three drying methods for mango slices: conventional hot air drying (HA), far-infrared combined hot air drying (FIRHA), and step-down temperature FIRHA. The effects of various operating parameters were analyzed, including drying medium temperature and the influence of far-infrared assistance, on the drying kinetics and quality attributes of the mango slices. The quality attributes assessed include color, shrinkage percentage, texture profile, water activity, microstructure, and energy consumption. The results indicate that the drying rates for FIRHA were significantly higher than those for HA. Mango slices dried using FIRHA and step-down temperature FIRHA exhibited greater lightness and greenness, along with increased crispness, while demonstrating lower yellowness compared to those dried by HA. The far-infrared assistance resulted in larger pore sizes and a higher void area fraction in the mango slices, but it also led to reduced hardness and shrinkage percentage compared to those dried using HA. In terms of specific energy consumption, the electric heater consumed significantly more energy than the far-infrared radiator and blower. Additionally, the total specific energy consumption of step-down temperature FIRHA was lower than that of both HA and FIRHA under all drying conditions. Based on these findings, this study recommends using step-down temperature FIRHA at 90°C for 1 h for the effective drying of mango slices, offering an optimal solution to the core challenges in the field. Ultimately, this work provides a valuable framework and empirical evidence for the adoption of hybrid drying technologies, contributing significantly to the fields of food engineering and sustainable agricultural processing. Key words: combined far-infrared-hot air drying; dried mango slices; drying kinetic; specific energy consumption; step-down temperature technique; texture DOI: 10.25165/j.ijabe.20251806.9770 Citation: Paengkanya S, Patcharatvirakul S, Kumklam P. Drying ripe mango slices using step-down temperature far-infrared-hot air techniques. Int J Agric & Biol Eng, 2025; 18(6): 281–289.